Type I Tibial Spine Fractures: Not So Simple to Classify, Not So Easy to Treat; A Multicenter Study. Issue 5 (31st May 2022) - Shimberg, Jilan L; Leska, Tomasina M; Aoyama, Julien T.; Cruz, Aristides I.; Ellis, Henry B.; Fabricant, Peter D.; Ganley, Theodore J.; Green, Daniel W.; Johnson, Benjamin; Kushare, Indranil; Lee, R. Jay; McKay, Scott; et al.
Background: Type I tibial spine fractures are non-displaced or minimally displaced (≤ 2mm displacement) fractures of the tibial eminence and ACL insertion traditionally managed nonoperatively with immobilization. Hypothesis/Purpose: We hypothesized that type I fractures do not carry significant risk of associated injuries and therefore do not require additional interventions aside from immobilization. Methods: We reviewed 52 patients classified by their treating institution with type I tibial spine fractures presenting between January 1, 2000 and January 31, 2019 at 10 institutions. Patients of age ≤ 18 years with pre-treatment plain radiographs and at least one year of follow-up were included. Data was collected on patient demographics, injury mechanism, treatment details, presence of concomitant injuries, range of motion (ROM) at final follow-up, treatment complications, and any return to the operating room for the injured knee. Pre-treatment imaging was reviewed by four authors to assess agreement of classification among the treating institutions. Patients were subclassified into two groups to ensure outcomes represented classic type I fracture patterns. Any patient with universal agreement among the four authors that the fracture did not appear consistent with a type I classification were assigned to Type 1+ Group (T1+). All other patients were assigned to the True Type I Group (TT1). We evaluated concomitant injury, need for operative intervention, and treatment outcomes overall and for each group independently. Results: 48 patients met inclusion criteria. 40/48 were TT1 fractures, while 8/48 were T1+ fractures, indicating less than universal agreement among sports specialists in classification of these fractures. Among TT1 patients, 7 of 40 (18.4%) underwent surgical treatment, though this represented 35.7% (5/14) of those who had undergone pretreatment advanced imaging. In the T1+ group, 6 of 8 (75%) underwent surgical treatment, 50% of whom (3/6) had pretreatment advanced imaging. Overall, twelve of 48 patients (25%) had concomitant injuries, nine TT1 patients and three T1+ patients (p=0.77), with 7 concomitant injuries requiring additional surgical management. Conclusions: Classification of type I fractures can be challenging. Nonetheless, a substantial percentage of patients with these fractures (>20%) were found to have concomitant injuries by advanced pretreatment imaging, with surgical management indicated in 58.3% of these patients. Contrary to traditional thought, type I tibial spine fractures do carry a risk of associated injuries. Simple cast immobilization may not be the ideal treatment in all cases. Advanced imaging would be beneficial for those whose plan of care may initially be non-operative treatment.